Investigating the relationship between women’s experience of intimate partner violence and utilization of maternal healthcare services in India - Pintu Paul (Nature Portfolio, 2021)
Abstract The utilization of maternal healthcare services is a key measure to reduce the incidence of maternal mortality. This study aims to examine the relationship between women’s exposure to intimate partner violence (IPV) and the utilization of maternal healthcare services, using a large-scale nationally representative data among Indian women. Data for this study were drawn from the fourth round of the National Family Health Survey (NFHS-4), which is collected during 2015–2016. In order to analyze, we utilized 24,882 currently married women aged 15–49 years who had at least one living child in the past five years preceding the survey. Women’s experience of IPV, which is manifested in various forms of physical, emotional, and/or sexual violence perpetrated by the partner, was considered as the key explanatory variable. Adequate antenatal care (ANC) [four or more ANC visits], delivery assistance by the skilled health provider, and postnatal care (PNC) within two days of delivery were used as outcome variables for assessing the utilization of maternal healthcare services. Descriptive statistics, cross-tabulation, Pearson’s chi-square test, and bivariate and multivariate logistic regression models were used in this study. Approximately 26% of the sample women (currently married) experienced any form of IPV in the past year. Bivariate analyses show that the utilization of all three components of maternal healthcare services was lower among women who experienced physical, sexual, or emotional violence, as compared to those who did not face any violence perpetrated by the partner. Multivariate analysis indicates that women’s exposure to IPV was significantly associated with a lower likelihood of adequate ANC utilization (Adjusted Odds Ratio [OR]: 0.90, 95% CI 0.84–0.97), even after controlling for socio-demographic characteristics. However, IPV had no significant relationship with skilled delivery assistance and unexpectedly a positive association with PNC usage (Adjusted OR: 1.09, 95% CI 1.02–1.16) in the adjusted analysis. Our study suggests formulating strategies toward the prevention of husband-perpetrated violence against women and targeting women who experienced spousal violence to improve their utilization of maternal healthcare services.